2016
DOI: 10.1007/s10231-016-0557-8
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity of four-dimensional compact manifolds with harmonic Weyl tensor

Abstract: ABSTRACT. The goal of this paper is to investigate the rigidity of 4-dimensional manifolds involving some pinching curvature conditions. To this end, we make use of the approach of biorthogonal curvature which is weaker than the sectional curvature. Here, we prove a rigidity result for 4-dimensional compact manifolds under a suitable lower bound condition on the minimum of the biorthogonal curvature. From this, we improve the pinching constants considered by some preceding works on a rigidity result for 4-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the sequel, as an application of Theorem 2 combined with results by Freedman [15] and Donaldson [14], we get the following corollary. It may be interesting to compare Corollary 1 with Theorem 1.3 in [26]. In fact, our latter result requires the same pinching condition of Theorem 1.3 in [26]; however, it does not require conditions on the Weyl tensor and analyticity of the metric.…”
Section: Theorem 1 Let (M 4 G) Be a Four-dimensional Compact Orienmentioning
confidence: 87%
See 1 more Smart Citation
“…In the sequel, as an application of Theorem 2 combined with results by Freedman [15] and Donaldson [14], we get the following corollary. It may be interesting to compare Corollary 1 with Theorem 1.3 in [26]. In fact, our latter result requires the same pinching condition of Theorem 1.3 in [26]; however, it does not require conditions on the Weyl tensor and analyticity of the metric.…”
Section: Theorem 1 Let (M 4 G) Be a Four-dimensional Compact Orienmentioning
confidence: 87%
“…In particular, they showed that a four-dimensional compact oriented Einstein manifold 1 10 -pinched is either topologically S 4 or homothetically isometric to CP 2 . Besides, the main result in [26] implies that a four-dimensional compact Einstein manifold M 4 with normalized Ricci curvature Ric = 1 and sectional curvature K ≥ 1 12 must be isometric to either S 4 or CP 2 ; see also [9,12,33]. Indeed, it remains a challenging task to obtain new classification results under weaker curvature pinching conditions.…”
Section: Introductionmentioning
confidence: 99%
“…where K ⊥ max (p) = max{K ⊥ (P); P ⊂ T p M}. More details can be found in [9,21] and references therein.…”
Section: Preliminariesmentioning
confidence: 99%
“…Moreover, it is not difficult to check that (λμ) 2 − 2λμ + 1 ≥ 0, for all λ, μ, which settles our claim (26). Proceeding, from inequalities (25), (21) and (26) we obtain…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…Furthermore, he showed that S4, mdouble-struckCP2nCP¯2 and n(double-struckS2×double-struckS2) admit metrics with positive biorthogonal curvature. For more details on this subject, see, for instance and .…”
Section: Introductionmentioning
confidence: 99%